1968
DOI: 10.1126/science.162.3858.1116
|View full text |Cite
|
Sign up to set email alerts
|

Infrasound at Long Range from Saturn V, 1967

Abstract: Two distinct groups of infrasonic waves from Saturn V, 1967, were recorded at Palisades, New York, 1485 kilometers from the launch site. The first group, of 10-minute duration, began about 70 minutes after launch time; the second, having more than twice the amplitude and a duration of 9 minutes, commenced 81 minutes after launch time. From information on the Saturn V trajectory and analysis of recorded data, it is established that the first group represents sound emitted either by the first stage reentry or by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Although early, single‐point observations indicated that shock acoustic waves excited by rocket launches can propagate as far as ~1500 km [ Donn et al , ], large‐area, long‐distance propagation of such waves has not previously been reported. Since a freely propagating acoustic wave would suffer from severe dissipation owing to kinematic viscosity, conductivity, and ion drag [ Drobzheva and Krasnov , ; Vadas and Nicolls , ], the waves' long‐distance propagation may result from ducting, which has been discussed extensively elsewhere [ Thome , ; Francis , ; Hunsucker , ; Ding et al , ; Matsumura et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Although early, single‐point observations indicated that shock acoustic waves excited by rocket launches can propagate as far as ~1500 km [ Donn et al , ], large‐area, long‐distance propagation of such waves has not previously been reported. Since a freely propagating acoustic wave would suffer from severe dissipation owing to kinematic viscosity, conductivity, and ion drag [ Drobzheva and Krasnov , ; Vadas and Nicolls , ], the waves' long‐distance propagation may result from ducting, which has been discussed extensively elsewhere [ Thome , ; Francis , ; Hunsucker , ; Ding et al , ; Matsumura et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…The atmospheric transit of rockets has been shown by Booker [1961], Jackson et al [1962], Kellogg [1964], Stone et al [1964], Felker and Roberts [1966], Donn et al [1968], Arendt [1971], Mendillo et al [1975], Zasov et al [1977], Behnke and Duncan [1980], Bernhardt et al [1988a, b], and others to produce a variety of atmospheric effects. Among these effects is the generation of propagating disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…The recent expansion of continuous GPS networks enabled the observations of growth and decay of such holes with sufficient spatial and temporal coverage. Infrasound has been often observed to accompany rocket launches (Donn et al, 1968). Calais and Minster (1996), using the GPS-TEC technique, detected such acoustic perturbation of the ionosphere, a physical influence of rocket ascent on ionosphere.…”
Section: Introductionmentioning
confidence: 99%